Social entrepreneurship and community transformation based on Islamic tasawur - Abdul Hamid, Solahuddin; Sa’ari, Che Zarrina; Abdul Rahman, Mohd Nizho; Ishak, Mohd Sobhi (Future Academy www.FutureAcademy.org.UK, 2018)
Human are made to live in community in nature. Life alone is unlikely because human nature and needs comes together naturally with its process of life. Entrepreneurial and its activities as part of Islamic Sharia’ is not merely for profit alone. Even entrepreneur offers charity services to community by fulfill their needs to get desired goods and services. This article will further describe about theoretical issues of ideas on standard basis which has been established by al-Quran and Hadith and Islamic scholars. Based on maqasid al-Shari’ah, the economy development in Islam is more stressed on human wellbeing (alfalah), better life (hayat tayyibah), concern on brotherhood (ukhuwwah) and socio-economy justice (’adalah) and also balanced satisfaction (qana’ah) whether in material and spiritual dimension. Human as agent in economy development, caliph as well as trustee need to work based on certain capacity to achieve it while being one is a test from Allah S.W.T. Hence, devoted to human is not the end of world for Islamic entrepreneurs. Meanwhile the absolute measure for this commercial is not limited to self satisfaction (entrepreneurs and customers) but include pleasure to work done, endowed by Allah S.W.T